ANALISA KUALITAS LAYANAN PADA CV. SINGOYUDHO NUSANTARA - Apriliana, Apriliana; Sukaris, Sukaris (Politeknik Negeri Ambon, 2022)
The purpose of this research is to identify service quality factors and identify ways that can be done to improve service quality. This research was conducted at CV.Singoyudho Nusantara which is located in Betoyokauman Village, Betoyokauman Village, Manyar Gresik District, East Java. This type of research is descriptive qualitative research. The data source used is the primary data source. Retrieval of data in this study using observation, interviews, and documents. The results that can be concluded in this study identify the quality of service that must be implemented by suppliers, namely being listed as a vendor who has AK3 and CSMS certificates, implementing 6 on namely on safety, on time, on scope, on quality, on cost and on clean, has work experience , the qualifications of the quality of the goods as evidenced by material tests and the speed of delivery and the payment system in the form of non-cash invoices. CV.Singoyudho Nusantara has implemented service quality, in the form of Reliability: levering accuracy, delivery speed is able to accommodate urgent goods. Assurance : polite appearance and in accordance with speech . Responsiveness: always responds quickly when problems occur. Assurance: always maintain politeness in both behavior and speech. Empathy: responsive and fast in communication. To increase customer satisfaction, the methods or strategies that can be implemented are to avoid miscommunication between CV.Singoyudho and customers, always respond quickly when contacted by customers and improve service quality according to standards in customer companies.